Motivation Patterns of Cyclists in the New-Normal Era - Vicki Ahmad Karisman (STKIP Muhammadiyah Kuningan, 2022)
This study aimed to determine the motivation pattern of the riders of mountain bikes, road bikes, and folding bikes in the new-normal era. The method used in this study is descriptive quantitative. The participants of this study were 258 cyclists in Bandung. The data was collected through a Sport Motivation Scale-6 questionnaire. This study indicates that there is no significant difference between the motivation of mountain bike, road bike, and folding bike riders. However, there is a substantial difference in income indicators in sociodemography, especially for road bike riders, while mountain bike and folding bike riders do not have any significant differences. This study shows that the motivation patterns of cyclists impact the cycling activities undertaken.